Economics for today - Tucker, Irvin B. (South-Western, Cengage Learning, 2014)
Help your students visualize economics in action. This book presents and reinforces core concepts, then immediately assesses student comprehension to ensure understanding. It provides a complement of instructor resources, including a handy Instructor's Resource CD, PowerPoint[registered] slides, and complete array of videos